1992
DOI: 10.1254/jjp.58.127
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Oxiracetam (CT-848) on Local Cerebral Glucose Utilization after Focal Cerebral Ischemia in Rats.

Abstract: -The effects of oxiracetam on the reduction of brain metabolism induced by focal cerebral ischemia were investigated by measuring local cerebral glucose uti lization (LCGU) in rats 24 hr after left middle cerebral artery occlusion. Focal cere bral ischemia reduced LCGU in the entire ipsilateral cortex, the greatest reduction being in the lateral parts of the frontoparietal cortex. LCGU was slightly reduced in the contralateral cortex; this reduction was considered to be caused by diaschisis. Ox iracetam was ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…60 Similar, regionally limited changes have been seen in rodents for ␤-amyloid precursor protein, CuZn-SOD, glial fibrillary acidic protein, isolectin B 4 -positive microglia, c-fos expression, and 2-deoxyglucose uptake. 35,44,[61][62][63] Chou et al 64 found CuZn-SOD and NADPH-d colocalized in motor neurons of ALS patients. Mn-SOD was not increased in NADPH-d positive neurons.…”
Section: 35mentioning
confidence: 99%
“…60 Similar, regionally limited changes have been seen in rodents for ␤-amyloid precursor protein, CuZn-SOD, glial fibrillary acidic protein, isolectin B 4 -positive microglia, c-fos expression, and 2-deoxyglucose uptake. 35,44,[61][62][63] Chou et al 64 found CuZn-SOD and NADPH-d colocalized in motor neurons of ALS patients. Mn-SOD was not increased in NADPH-d positive neurons.…”
Section: 35mentioning
confidence: 99%
“…In this study, the MSI results showed that the levels of glucose and citric acid increased, whereas the levels of ATP, ADP, and AMP decreased after the 2-VO surgery. The increase in glucose caused by the 2-VO surgery was likely due to the lower glucose utilization in the brain as suggested by a previous report 53 . The increased levels of citric acid and decreased levels of downstream products, including glutamate and aspartate, could have been caused by the arrest of the TCA cycle at the step from citrate to α-ketoglutarate.…”
Section: Discussionmentioning
confidence: 52%
“…Glucose is the key source of energy in the brain, and citric acid is the first mediator of the Tricarboxylic acid (TCA) cycle. Previous studies have shown that oxiracetam increases glucose utilization in cerebral ischemic rats 53 . In this study, the MSI results showed that the levels of glucose and citric acid increased after the 2-VO surgery.…”
Section: Discussionmentioning
confidence: 89%
“…In recent years, there is an increasing clinical application of nootropic drugs for the therapy of central nervous system diseases such as traumatic brain injury and cerebral hemorrhage. Previous evidences suggested that Oxiracetam, a new nootropic drug, improved local cerebral glucose utilization (Hokonohara, Sako, Shinoda, Tomabechi, & Yonemasu, 1992) promoted the synthesis of proteins and nucleic acids, and produced a protective effect in cerebrovascular damage (Kometani et al, 1991). Another study clearly indicated Oxiracetam inhibited cells apoptosis in brain tissues and facilitated neurological function recovery .…”
Section: Introductionmentioning
confidence: 99%